The Complete Flutter and Dart App Development Course - Dichone, Paulo (Packt Publishing, 2020)
Learn Flutter - Google's mobile development framework - and build Flutter iOS and Android apps using a single codebase About This Video Get an introduction to Flutter and understand Flutter app anatomy Design, build, and debug Flutter Android and iOS apps Explore the capabilities of Flutter to build robust apps In Detail The Complete Flutter and Dart App Development Course is the first comprehensive Dart and Flutter course, fully updated to include the latest developments. Flutter is the new cross-platform mobile app development framework created by Google that allows developers to build Android and iOS apps using a single codebase, and it is the best way to develop cross-platform apps, which would otherwise require two distinct mobile development teams. Instead of having to learn Objective-C or Swift to build iOS apps, and Java or Kotlin to build Android apps, you can now use Flutter to build apps that run natively in both iOS and Android devices using the general-purpose programming language Dart. The course begins with an overview of Flutter's capabilities and helps you to download Flutter code and set up development tools for Windows and Mac. It then gives you a comprehensive introduction to Dart and covers the fundamentals and advanced concepts of object-oriented programming (OOP). As you advance, you'll get to grips with Flutter's intermediate concepts and themes. Toward the end, you will build a Flutter tip calculator app and take up quizzes and challenges relating to Flutter widgets and material design. By the end of this course, you'll have gained complete knowledge of Flutter and be able to build both iOS and Android apps like a professional.